2016
DOI: 10.1371/journal.pone.0163828
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide Distribution of Bovine Influenza D Virus Infection in Japan

Abstract: Cattle are major reservoirs of the provisionally named influenza D virus, which is potentially involved in the bovine respiratory disease complex. Here, we conducted a serological survey for the influenza D virus in Japan, using archived bovine serum samples collected during 2010–2016 from several herds of apparently healthy cattle in various regions of the country. We found sero-positive cattle across all years and in all the prefectural regions tested, with a total positivity rate of 30.5%, although the posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
52
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 18 publications
1
52
2
Order By: Relevance
“…However, several metagenomic analyses have suggested that this virus plays an important role as an inducer of BRD (Mitra et al., ; Ng et al., ). The diffuse seropositivity of cattle in Japan and the full‐genome sequence of a Japanese strain of the influenza D virus (D/bovine/Ibaraki/7768/2016) have already been reported by Horimoto's group (Horimoto et al., ; Murakami et al., ). D/bovine/Ibaraki/7768/2016 has several unique amino acids and is genetically distant from strains found in other countries.…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, several metagenomic analyses have suggested that this virus plays an important role as an inducer of BRD (Mitra et al., ; Ng et al., ). The diffuse seropositivity of cattle in Japan and the full‐genome sequence of a Japanese strain of the influenza D virus (D/bovine/Ibaraki/7768/2016) have already been reported by Horimoto's group (Horimoto et al., ; Murakami et al., ). D/bovine/Ibaraki/7768/2016 has several unique amino acids and is genetically distant from strains found in other countries.…”
Section: Introductionmentioning
confidence: 79%
“…However, both strains from Japan possessed serine at this position. A previous antibody survey revealed that the antigenicity of D/bovine/Ibaraki/7768/2016 was more similar to D/OK‐type than to D/660‐type (Horimoto et al., ). However, the antigenicity difference between D/OK‐type and the Japanese strain (D/Japan‐type) remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological analyses revealed that cattle are the main host of the virus, due to their high seroprevalence for IDV (2, 3). Further epidemiological studies revealed that IDVs circulate in cattle in many countries including the USA (24), Mexico (5), China (6), Japan (7, 8), France (9), Italy (10), Ireland (11), Luxembourg (12), and African countries (13). Furthermore, serological studies showed that IDV antibodies are found in pigs (14), sheep (15, 16), goats (15, 16), dromedary camels (13, 17), horses (18), and humans (19).…”
Section: Introductionmentioning
confidence: 99%
“…Since its discovery, both IDV and anti-IDV antibodies have been successfully detected in North and Central America, Europe, Asia, and Africa (12,(14)(15)(16)(17)(18)(19)(20)(21). While IDV is thought to be circulating among several mammalian species (14), cattle are considered to be the primary host and reservoir.…”
mentioning
confidence: 99%